2015
DOI: 10.1002/micr.22382
|View full text |Cite
|
Sign up to set email alerts
|

Supermicrosurgical deep lymphatic vessel‐to‐venous anastomosis for a breast cancer‐related arm lymphedema with severe sclerosis of superficial lymphatic vessels

Abstract: Lymphatic supermicrosurgery or supermicrosurgical lymphaticovenular anastomosis (LVA) is becoming popular for the treatment of compression-refractory upper extremity lymphedema (UEL) with its effectiveness and minimally invasiveness. In conventional LVA, superficial lymphatic vessels are used for anastomosis, but its treatment efficacy would be minimum when superficial lymphatic vessels are severely sclerotic. Theoretically, deep lymphatic vessels can be used for LVA, but no clinical case has been reported reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Severe sclerosis was observed in superficial lymphatics in the upper limb of a patient with refractory BCRL of 18 years' duration. 43 Inflammatory triggers for the above might be aggravated by the association between obesity and an abnormal inflammatory response, perhaps involving macrophage migration.…”
Section: Hypothesis Linking Raised Ppump In Pre-bcrl and Subnormal Ppmentioning
confidence: 99%
“…Severe sclerosis was observed in superficial lymphatics in the upper limb of a patient with refractory BCRL of 18 years' duration. 43 Inflammatory triggers for the above might be aggravated by the association between obesity and an abnormal inflammatory response, perhaps involving macrophage migration.…”
Section: Hypothesis Linking Raised Ppump In Pre-bcrl and Subnormal Ppmentioning
confidence: 99%
“…In patients with this scenario, an LVA can still be effective if performed properly despite the fibrosis and sclerosis of the superficial lymphatic channels. 45 Other institutions that perform lymphedema surgery have also demonstrated similar outcomes; however, certainly, the number of institutions with high-volume and long-term outcomes are limited. Studies have demonstrated a certain percentage of thrombosis or sclerosis of the bypasses following an LVA, which can lead to recurrent lymphedema and swelling over time.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic venous anastomosis (LVA) using a microsurgical approach has become increasingly popular for patients needing lymphatic surgery. Although most advanced staged patients often have highly stenotic and fibrotic lymphatic vessels (Yamamoto, Yamamoto, Hayashi, & Koshima, 2017), some retain strong flow and can still achieve effective LVA. Small-caliber veins are usually dissected to minimize any size discrepancy.…”
Section: Dear Editormentioning
confidence: 99%